PEMBERIAN UREA DAN URIN SAPI PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Sabto Bintoro; Sampurno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was to determine the effect of urea and cow urine application on the growth of oil palm (Elaeis guineensis Jacq.) in main nursery. The research used Completely Randomized Design (CRD) consist of 16 treatments with three replications. The treatment given is giving urea and cow urine with concentrations as follows: Factor I, giving urea; U0: 0 g urea/polybag with 10 kg of top soil, U1: urea 0.91 g/polybag with 10 kg of top soil, U2: urea 1.82 g/polybag with 10 kg of top soil and U3: urea 3.64 g/polybag with 10 kg of top soil. Factor II, giving cow urine; K0: cow urine 0 cc/l of water, K1: cow urine 40 cc/l of water, K2: cow urine 45 cc/l of water and K3: cow urine 50 cc/l of water. Data obtained from this research were statistically analyzed by Analysis of Variance and further test DNMRT at 5% level. Parameters observed were: plant height growth, diameter of hump growth, number of leaves gain, root volume and plant fresh weight. The results show that interactions of giving urea and cow urine significantly affect to parameters diameter of hump growth, number of leaves gain, root volume and plant fresh weight. Giving urea 1,82 g/polybag and cow urine at concentrations of 45 cc/l of water is the best applcations for oil palm growth in main nursery.   Keywords : urea, cow urine, main nursery